CONSTRUCCIÓN DEL PERSONAJE ADOLESCENTE EN LA FICCIÓN SERIADA EUROPEA. LAS SERIES ORIGINALES DE NETFLIX COMO CASO DE ESTUDIO - Ldo. Daniel FERRERA (Fonseca, Journal of Communication, 2023)
This paper analyses the construction of the teenage character in European serial fiction through the analysis of 23 Net-flix Originals with a methodology that combines quantitative and analytical-descriptive elements.. To establish the dif-ferences and parallels between the teenage characters of the different European series, a total of 132 characters have been classified around 18 variables of analysis, focusing on issues of representation and aspects of the storyline, emphasizing the importance of the peer group for the teenage character, as well as the existence of a behavior that, sometimes, is in-consistent with the age it portrays.